Analisis Pengaruh Citra Lembaga, Kualitas Layanan dan Religiusitas terhadap Keputusan Muzaki Membaya Zakat dengan Minat sebagai Variabel Moderating - Iin Sofiyani; Agus Kristiyono (Jesya (Jurnal Ekonomi dan Ekonomi Syariah), 2020)
The purpose of this research is to determine the effect of institutional image, service quality, and religiosity, on the decision of muzaki to pay zakat in LazisMu, using interest as a moderating variable. The research was conducted at Lazis Mu sub-district Suruh, Semarang regency. The population of this quantitative research is muzaki LazisMu in sub-district Suruh, Semarang Regency with 112 people. This research is classified as quantitative. The sample is determined by using a simple random sampling technique. The analytical method used in this research is linear regression analysis using SPSS. The test is being used to collect data in questionnaires, literature review, and documentation Before a test give to real samples, the test was tested using validity and reliability. The data analysis techniques in this research use descriptive statistical analysis, test classical assumptions, and multiple linear regression. The results of this research stated that institutional image and religiosity are not influenced by the decision of muzaki to pay zakat, while the quality of service affected the decision of muzaki to pay zakat on LazisMu. The research shows that interest moderates the influence of institutional image, service quality, and religiosity, on the decision of muzaki to pay zakat at LazisMu Branch Suruh.